Biodegradation Study of Potato Starch-Based Bioplastic - Kundu, Rajen; Payal, Priyanka (Current Chinese Chemistry, 2022)
Background: Plastics are indispensable for our society. The extensive use of petroleum-based plastic and dumping of the same in soil and water body greatly affects our environment and biodiversity. However, biodegradable plastics can reduce the volume of waste in packaging materials. Therefore, biomass-derived polymers are promising alternatives to the petroleum-based non-degradable polymer to address the environmental issues.Objective: A large number of reports on the synthesis and characterization of starch-based bioplastic are available in the literature. However, a detailed biodegradation study of the starch-based bioplastic is rarely reported. We have prepared potato starch-based bioplastic with the combination of various plasticizers (glycerol, sorbitol, and xylitol) through hydrogel formation and carried out their biodegradation study.Methods: Present study investigated the biodegradation of potato starch-based bioplastic in the natural environment, in cultured bacteria, and with fungal α-amylase.Results: Starch-based plastic is completely degraded in the natural environment within two months. Bacteria culture in solid media resulted in various types of bacterial colonies. Among the various bacterial colonies, the white circular colony was the major bacteria that degrade starch-based plastic. Furthermore, we screened the starch-based plastic degrading bacteria and isolated the pure culture through the streak plate method.Conclusion: In the presence of cultured bacteria and with fungal α-amylase, starch-based plastic is completely degraded within 96 h and 48 h, respectively.
Keywords: Biodegradation